Ultrafast isomerization-induced cooperative motions to higher molecular orientation in smectic liquid-crystalline azobenzene molecules - Masaki Hada (Nature Portfolio, 2019)
Photoisomerization of molecules is used to control the structure of soft matter but the response of molecules during isomerization is difficult to elucidate. Here the authors describe ultrafast formation of higher-orientation of liquid-crystalline azobenzene molecules via linearly polarized UV light using time-resolved electron diffraction.